Tinjauan Teori Al-Mashlahah Al-Buthi Terhadap Hak Anak dalam Perspektif Hukum Islam dan Perjanjian Internasional - Achmad Shobirin Hasbulloh; Ahmadi Hasan; Masyithah Umar (Sharia Journal and Education Center Publishing, 2023)
Abstract This paper discusses children's rights in the perspective of Islamic law and international treaties and compares them using al-Buthi's al-mashlahah theory contained in his book entitled